2015
DOI: 10.1002/jib.264
|View full text |Cite
|
Sign up to set email alerts
|

The nutritional, biochemical and health effects of makgeolli - a traditional Korean fermented cereal beverage

Abstract: Makgeolli is a traditional alcoholic beverage prepared from rice, barley, wheat or malt grains by fermentation using a natural starter called nuruk. The makgeolli flavour depends mainly on the content of the metabolic products (free sugars, amino acids, organic acids and aromatic compounds) produced during the fermentation of rice by moulds and yeasts. Compared with other alcoholic beverages, makgeolli contains high concentrations of nutrients, organic acids and 6-8% alcohol. Makgeolli is nutritious and is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Thus, during fermentation, R. oligosporus might bio‐convert bound‐phenolic compounds into unbound phenolics as aglycone forms (Huynh et al., 2014). Furthermore, during the process of brewing Makgeooli, different kinds of fungi ( Aspergillus , Rhizopus ), yeast, and various lactic acid bacteria (Nile, 2015) can produce tannase, phenolic acid decarboxylase, benzyl alcohol dehydrogenase, and β‐glucosidase that can degrade some phenolic compounds (Landete et al., 2010). Therefore, fermentation processes might release phenolic compounds from plant matrixes followed by metabolic pathways of flavonoids, including glycosylation, deglycosylation, ring cleavage, methylation, glucuronidation, and sulfate conjunction in ways to produce new bioactive compounds (Huynh et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, during fermentation, R. oligosporus might bio‐convert bound‐phenolic compounds into unbound phenolics as aglycone forms (Huynh et al., 2014). Furthermore, during the process of brewing Makgeooli, different kinds of fungi ( Aspergillus , Rhizopus ), yeast, and various lactic acid bacteria (Nile, 2015) can produce tannase, phenolic acid decarboxylase, benzyl alcohol dehydrogenase, and β‐glucosidase that can degrade some phenolic compounds (Landete et al., 2010). Therefore, fermentation processes might release phenolic compounds from plant matrixes followed by metabolic pathways of flavonoids, including glycosylation, deglycosylation, ring cleavage, methylation, glucuronidation, and sulfate conjunction in ways to produce new bioactive compounds (Huynh et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The higher antioxidant activity of buckwheat and fermented buckwheat Makgeolli compared to rice Makgeolli might be due to the presence of l-carnitine, tocopherols, phenolic substance such as 3-flavanols, rutin, phenolic acids, and their derivatives in buckwheat which are known to possess antioxidant activity (Holasova et al, 2002;Oomah et al, 1996) (Huynh et al, 2014). Furthermore, during the process of brewing Makgeooli, different kinds of fungi (Aspergillus, Rhizopus), yeast, and various lactic acid bacteria (Nile, 2015) can produce tannase, phenolic acid decarboxylase, benzyl alcohol dehydrogenase, and β-glucosidase that can degrade some phenolic compounds (Landete et al, 2010).…”
Section: Analyses Of Rutin Quercetin L-carnitine and Antioxidantmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,17] The saccharification of starches in makgeolli likely provides the precursor sugars such as glucose required for the biosynthesis of FOH and SQ. [2,28] Although our SE-GC/MS method did not detect FOH or SQ in beer or wine, which may be present in very low amounts, we successfully identified measurable levels of these compounds in makgeolli samples using our newly developed method.…”
Section: Application To Various Alcoholic Beverage Samplesmentioning
confidence: 95%
“…Accumulating evidence has revealed that makgeolli has various biological effects in vitro, suggestive of anticancer, anti-inflammatory, and antioxidant properties. [2] Animal studies have also demonstrated that oral administration of makgeolli elicits antitumor effects in a gastric tumor xenograft mouse model [3] and antioxidant activity in rat blood plasma. [4] Various bioactive compounds such as organic acids [5,6] and polyphenols [7] have been identified in makgeolli, as well as several volatile compounds.…”
Section: Introductionmentioning
confidence: 99%